Phase equilibria of the ternary systems of (water + diethyl carbonate) with acetone, or 2-butanone at four temperatures. (November 2016) - Wang, Cui; Chen, Yao; Cheng, Kai; Wen, Caiyu
Highlights: LLE data of water + acetone (or 2-butanone) + diethyl carbonate (DEC) were measured at four temperatures. LLE data were correlated by using the extended and modified UNIQUAC models. Distribution coefficients and separation factors were calculated. Abstract: (Liquid + liquid) equilibrium (LLE) for the ternary systems of water + acetone + diethyl carbonate (DEC) and (water + 2-butanone + DEC) were determined at T = (293.15, 298.15, 303.15, 313.15) K and p = 100 kPa. The reliability of the experimental LLE was verified by the Othmer-Tobias and Bachman equations. The experimental LLE values were correlated with the modified and extended UNIQUAC models. Distribution coefficients and separation factors were calculated from the LLE data to evaluate the extraction capability of the organic solvents.